Synthesis of aza-BODIPYs with barrier-free rotation of the –tBu group at 3-site and enhancement of photothermal therapy by triggering cancer cell apoptosis. Issue 41 (4th October 2022) - Zhao, Junzhu; Wang, Huan; Zhang, Dongxiang; Shen, Yue; Zhang, Shan; Ren, Junyi; Wang, Zhan; Sun, Ya-nan; Du, Jianjun; Jiang, Xin-Dong; Wang, Guiling
Abstract : Development of aza-BODIPY with barrier-free rotation of the – t Bu group at 3-site provided a strong platform for the design of a photothermal therapy agent for cancer treatment by apoptosis. Abstract : Breaking through the traditional 1, 7, 3, 5-aryl substituted aza-BODIPY structure, asymmetric aza-BODIPYs, t Bu-azaBDPs, containing non-aryl group at 3-site were prepared for the first time. t Bu-azaBDP exhibited a severely twisted configuration. t Bu-azaBDPs had a near-infrared fluorescence emission and high molar extinction coefficients. Although the barrier-free rotation of the distal – t Bu group in t Bu-azaBDP resulted in low fluorescence quantum yield, the photothermal conversion efficiency was markedly enhanced. t Bu-azaBDP nanoparticles with laser irradiation were revealed to induce cell apoptosis in photothermal therapy. We consider that development of aza-BODIPYs with the barrier-free rotation of the – t Bu group at 3-site provides a strong platform for design of phototherapy agents for cancer treatment in photothermal therapy by apoptosis.